2022
DOI: 10.1080/26410397.2022.2048455
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of marital rape and sexual violence within marriage in India: evidence from service records

Abstract: Sexual violence within marriage is common and manifests in various forms, including marital rape. It has serious physical and mental health consequences and is a violation of women’s sexual and reproductive health rights. Marital rape, reproductive coercion, inserting objects in the vagina or anus, and withholding sexual pleasure are forms of violence routinely experienced by women. Based on service records of survivors coming to public hospitals in an Indian city, this paper presents their pathways to disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The reporting of sexual abuse was low, which may be due to under-reporting or cultural differences as no court law is available to punish the perpetrators. Although, the religion, Islam, has explicitly forbidden to use of any sort of emotional or physical force pertaining to the sexual relationship between the married couple; however, marital rape (forceful intercourse by the spouse) is not defined as abuse (Deosthali et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The reporting of sexual abuse was low, which may be due to under-reporting or cultural differences as no court law is available to punish the perpetrators. Although, the religion, Islam, has explicitly forbidden to use of any sort of emotional or physical force pertaining to the sexual relationship between the married couple; however, marital rape (forceful intercourse by the spouse) is not defined as abuse (Deosthali et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While the number of rape cases reported annually in the United States is 10 times greater than that in India (Statista 2021), the numbers are skewed since less than 1% rapes in India are reported (Raj and McDougal 2014). Furthermore, reports have indicated that one in three women in India have experienced some form of sexual coercion or violence (see Deosthali, Rege, and Arora 2022). The court is split on the issue of criminalizing marital rape; in May 2022, a two-judge bench of the Delhi High Court issued a split decision on the problem.…”
Section: Brahmanical Patriarchymentioning
confidence: 99%
“…IPVAW and its psychosocial effects are grounded in wider, socially sanctioned, systems of abuse and mistreatment of women. In both Asia and sub-Saharan Africa, marital rape and sexual degradation is widespread and is often depicted in customary law as a husband’s prerogative [ 64 , 65 ]. Widespread acceptance of marital rape and the absence of or failures to enforce laws against rape inside the family can leave women feeling fearful and without protection.…”
Section: The Psychosocial Impact Of Ipvaw In Social Ecological Perspe...mentioning
confidence: 99%